Carboxyl-functionalized task-specific ionic liquids for solubilizing metal oxides - Nockemann, Peter; Thijs, Ben; Parac-Vogt, Tatjana N; Van Hecke, Kristof; Van Meervelt, Luc; Tinant, Bernard; Hartenbach, Ingo; Schleid, Thomas; Ngan, Vu Thi; Nguyen, Minh Tho; Binnemans, Koen (Inorganic chemistry, 2008)
Imidazolium, pyridinium, pyrrolidinium, piperidinium, morpholinium, and quaternary ammonium bis(trifluoromethylsulfonyl)imide salts were functionalized with a carboxyl group. These ionic liquids are useful for the selective dissolution of metal oxides and hydroxides. Although these hydrophobic ionic liquids are immiscible with water at room temperature, several of them form a single phase with water at elevated temperatures. Phase separation occurs upon cooling. This thermomorphic behavior has been investigated by (1)H NMR, and it was found that it can be attributed to the temperature-dependent hydration and hydrogen-bond formation of the ionic liquid components. The crystal structures of four ionic liquids and five metal complexes have been determined.